2021
DOI: 10.1186/s40634-020-00318-7
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing complications in bikini incision direct anterior approach total hip arthroplasty: A single surgeon series of 865 cases

Abstract: Purpose The purpose of this study was to report all complications during the first consecutive 865 cases of bikini incision direct anterior approach (DAA) total hip arthroplasty (THA) performed by a single surgeon. The secondary aims of the study are to report our clinical outcomes and implant survivorship. We discuss our surgical technique to minimize complication rates during the procedure. Methods We undertook a retrospective analysis of our com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…In our study, we found a higher overall number of complications requiring revision surgery but no statistically significant differences in the rate of infections comparing the 3 groups: only 1 out of 72 patients had a wound infection requiring revision surgery, an incidence lower than previously reported [14]. In addition, Avinash et al reported a low rate of infection, specifically, of 0.58%, in a study of more than 800 THAs in a population with an average BMI of 28 [32]. These data could support the protective role of minimally invasive DAA against infections, even in high-risk OB patients [33].…”
Section: Discussioncontrasting
confidence: 48%
“…In our study, we found a higher overall number of complications requiring revision surgery but no statistically significant differences in the rate of infections comparing the 3 groups: only 1 out of 72 patients had a wound infection requiring revision surgery, an incidence lower than previously reported [14]. In addition, Avinash et al reported a low rate of infection, specifically, of 0.58%, in a study of more than 800 THAs in a population with an average BMI of 28 [32]. These data could support the protective role of minimally invasive DAA against infections, even in high-risk OB patients [33].…”
Section: Discussioncontrasting
confidence: 48%
“…While the exact mechanism is unclear, bikini incision may raise the risk of injury to the LFCN branches due to greater medial extension over the tensor fasciae latae and reduced intraoperative field, sometimes requiring more forceful retraction [ 9 , 21 , 23 ]. Interestingly, evidence shows that LFCN symptoms improve significantly and spontaneously with time [ [24] , [25] , [26] , [27] ], so early LFCN injury may not ultimately be an important indicator of surgical success. Further study of these outcomes in larger prospective trials is warranted.…”
Section: Discussionmentioning
confidence: 99%